Benefit-cost analysis of Automotive Lightweighting Material projects. (30th November 2004) - Das, Sujit; Tonn, Bruce E.; Peretz, Jean H.
This paper presents benefit-cost analyses for three R&D projects funded by the Automotive Lightweighting Materials Program of the US Department of Energy: design and product optimisation for cast light metals; durability of lightweight composite structures; and rapid tooling for functional prototyping of metal mould processes. Market penetration rates for new technologies from these projects were estimated from 2002 to 2025. A life-cycle approach was used to estimate energy, environmental, and security benefits. Costs include total project costs and estimates of industry costs to commercialise the new technologies. Benefit-cost ratios were estimated under three sets of assumptions. The ratios were substantial in all cases. The results suggest that collaborative efforts between government and industry in the area have tremendous potential.